Factors influencing the hospital length of stay in Covid-19 patients in Calicut, Kerala - A cross-sectional study - Pratibha Dabas; Harsha P.V.; Sneha Henry; Manisha Wadhwa; Kanniyan Binub (Global Journal of Medicine and Public Health, 2024)
Background During the recent Covid-19 pandemic, the illness spread around the globe with about 346 million confirmed cases and over 5.5 million deaths. There was varied morbidity and mortality among patients. In this study, we evaluated the association of sociodemographic parameters and Covid-19 vaccination with the hospital length of stay for covid patients.